Synergistic effect of acidic-basic features of copper-doped layered double hydroxides nanocatalysts in valorization of biomass-derived furfural to biofuels - Gode, Nilesh G.; Nagpure, Atul S.; Rewatkar, Suresh B.; Bhagat, Shailesh K.; Deshmukh, Ganpat D.; Saini, Ajay (ChemPlusChem, 2025)
Valorization of biomass-derived chemicals into high-quality compounds and biofuels is enormously fundamental to diminish dependence on fossil-based resources. Furfural is a bio-based valuable compound which can be proficiently upgraded to 4-(2-furyl)-3-buten-2-one (FAc) and 1,4-pentadiene-3-one, 1,5-di-2-furanyl (F 2 Ac) via aldol condensation of furfural with acetone. In the present work, efficient Cu-doped Mg-Al layered double hydroxides (LDH) nanocatalysts are fabricated by coprecipitation and are exploited for furfural conversion to obtained FAc and F 2 Ac. The structure-activity relationship is scrutinized by characterizing fresh and spent nanocatalysts via numerous techniques. The good correlation between the amount of weak acidic-weak basic catalytic sites and nanocatalysts performance is established. The superior performance of Cu-0.1 nanocatalyst (Cu-content = 1.85 wt%) in aldol condensation is attributed to the presence of optimum weak acidic sites (0.21 mmol g-1) and weak basic sites (0.36 mmol g-1), synergistic acidic-basic effect, nano-sized Cu(OH) 2 nanoparticles (1.6 nm), high BET surface area (181 m2 g-1), and mesoporous architecture of material. Cu-0.1 nanocatalyst delivered 98% FAc selectivity with 100% furfural conversion at 85 degrees C. Furthermore, at 100 degrees C, the nanocatalyst gives 55% F 2 Ac selectivity with 73% furfural conversion. The catalyst displays good recyclability (7 recycles) and stability. Plausible mechanistic pathway for transformation of furfural to FAc and F 2 Ac is proposed.
Keywords: Aldol condensation; biofuels; biomass valorization; nanocatalysis; synergistic effect

Upgradation of biomass-derived furfural by nanostructured layered double hydroxides: Influence of stirring rate on structural features of materials - Bhagat, Shailesh K.; Nagpure, Atul S.; Lanjewar, Mamata R.; Gode, Nilesh G.; Deshmukh, Ganpat D.; Saini, Ajay (Inorganic Chemistry Communications, 2025)
The proficient conversion of biomass-derived compounds into the high-quality platform chemicals and bio-fuels is enormously imperative to decrease dependence on fossil feedstock. Furfural is a significant bio-based chemical which can be efficiently converted to valuable 4-(2-furyl)-3-buten-2-one (FAc) via aldol condensation. In this work, we have developed prominent layered double hydroxides (LDHs) catalysts for mild aldol condensation of furfural and acetone to acquired high performance with admirable FAc selectivity. Various nanostructured Mg-Al LDHs were synthesized through co-precipitation procedure under different stirring rate conditions. The structural, morphological and optical attributes of materials as well as recyclability aspect and structure-activity relationship was examined by characterizing the fresh and spent catalysts via numerous techniques (XRD, N2 sorption, DLS, CO2-TPD, NH3-TPD, FT-IR, UV-Visible spectroscopy, TGA, SEM, TEM, ICP-OES, 27Al NMR spectroscopy, XPS, Raman spectroscopy, etc). Several reaction parameters were also optimized. Among the catalysts tested, LDH-1200 catalyst exhibits outstanding performance by delivering 100% furfural conversion with 99% FAc selectivity. Moreover, catalyst illustrates excellent recyclability and stability. The mechanistic insight for aldol condensation was also investigated by monitoring the intermediates at different stages and intervals during the course of the reaction. This study confirms that stirring rate has significant influence on physico-chemical attributes of materials and the amount of weak basic sites plays imperative role in catalytic performance.
Keywords: Aldol condensation; Biomass-derived compounds; Flower-shaped nanocrystals; heterogeneous catalysis; Nanostructured mesoporous LDH